Fault diagnosis for satellite attitude control systems with four flywheels - Wang, Zhenhua (2018)
This paper proposes a novel fault diagnosis approach for the satellite attitude control system with flywheel faults. The key contributions include fault estimation by sparse approximation algorithm and diagnosis of multiple faults. In this paper, a Taylor series expansion is used to derive a fault estimation representation. Based on the sparse property of the faults, fault estimation is formulated as a sparse approximation problem and solved using the orthogonal matching pursuit (OMP) algorithm. Simulation results demonstrate the effectiveness of the proposed method.